The voyages of Doctor Dolittle - Lofting, Hugh, 1886-1947. (New York, New York : Bantam Doubleday Dell Books for Young Readers, 1988)
When his colleague Long Arrow disappears, Dr. Dolittle sets off with his assistant, Tommy Stubbins, his dog, Jip, and Polynesia the parrot on an adventurous voyage over tropical seas to floating Spidermonkey Island.
Keywords: Children's literature -- Fiction; Fiction